2015
DOI: 10.1007/s00192-015-2660-6
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle function in women with provoked vestibulodynia and asymptomatic controls

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Naess, I., Bø, K. (2015). Pelvic floor muscle function in women with provoked vestibulodynia and asymptomatic controls. Young, nulliparous women with provoked vestibulodynia had higher vaginal resting pressure, but not higher vaginal surface EMG activity, pelvic floor muscle strength or endurance, than controls. Short version of title:Pelvic floor muscles function and provoked vestibulodynia Conclusion: Young, nulliparous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 24 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Previous psychophysical testing of women with vulvodynia has demonstrated differences in pain sensitivity compared to control women [3, 5, 7, 24]. Localized [3, 4, 6, 7] as well as systemic [4, 6] tenderness to pressure among women with vestibulodynia or vulvodynia compared to controls has been demonstrated repeatedly, suggesting a central nervous system “sensitization” associated with vulvodynia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous psychophysical testing of women with vulvodynia has demonstrated differences in pain sensitivity compared to control women [3, 5, 7, 24]. Localized [3, 4, 6, 7] as well as systemic [4, 6] tenderness to pressure among women with vestibulodynia or vulvodynia compared to controls has been demonstrated repeatedly, suggesting a central nervous system “sensitization” associated with vulvodynia.…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of A number of mechanisms have been suggested as the pathophysiological basis of CPPS: (1) An infection process, but no conclusive evidence has been found and antibiotic treatment is ineffective; (2) A neurogenic inflammation that includes local chemical changes [1,7]; (3) Hypoxia. A disrupted blood flow to the pelvic area, reduced micro-vascular density of the bladder's submucosa layer, followed by decreased perfusion [19] is supported by clinical improvement following hyperbaric treatment [20][21][22]; and (4) Weakness or cramps of the pelvic floor muscles [13,23]. None of the above have been mentioned as the sole cause of the syndrome, and it is estimated that these mechanisms interact.…”
Section: Search Strategymentioning
confidence: 98%
“…Manual examination of the pelvis may find tension, rigidity, and sensitivity of the pelvic floor muscles or myofascial trigger points. PVD refers to pain at the entrance of the vagina, known as the vestibule, experienced as sharp or burning pain that lasts at least three months [12][13][14]. The diagnosis criteria for PVD may include severe pain when touched or when vaginal penetration is attempted, soreness located in the vestibule without similar soreness in adjacent tissues, and ruling out other factors (infection, inflammation, skin disease, etc.)…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…and Mathur C. et al [ 48 ] indicated that women presenting as underweight or obese were significantly less likely to have it than those with a normal BMI. On the other hand, the results obtained by Naess I and Bø K. [ 49 ] show that the average BMI of people with chronic vulvar pain was normal and was approximately 22. The results of our study are consistent with these data.…”
Section: Discussionmentioning
confidence: 96%